ANALISIS PRODUKSI KUBIS (Brassica oleracea L) DITINJAU DARI FUNGSI-FUNGSI DAN EFISIENSI PEMASARAN - Sinaga, Asmina Herawaty; Rajagukguk, Salome (JURNAL DARMA AGUNG, 2024)
The objectives of this study were (1) to determine the cabbage marketing channel, (2) the difference in marketing costs, profit sharing margin, and price difference in each marketing channel, (3) to determine the level of efficiency in each cabbage marketing channel in the study area. The research area was determined by purposeful sample selection in the village of Merek, Kecamatan Merek, Kabupaten Karo which was conducted in April 2019-July 2019. The reason for choosing the area is because the majority of the population makes a living from cabbage farming. The sampling method was conducted by simple random sampling. The sample in this study were farmers who make a living from cabbage farming throughout the year. The number of samples in this study was 33 samples. The results showed that: There are 3 cabbage marketing channels in the study area, channel I (farmers-traders-large traders-retail traders-consumers), channel II (farmers-large traders-retail traders-consumers), and channel III (farmers-retail traders-consumers). Cabbage marketing costs from farmers to the largest consumers are in channel I of Rp.1,082.54/kg compared with marketing costs in channel II of Rp.756.26/kg, and marketing costs in channel III of Rp.361.67/kg. Efficiency in each cabbage marketing channel is channel I by 18.78%, channel II by 12.82% and channel III by 6.03%, this means that marketing channel III is more efficient than marketing channels I and II.